design and implementation of smart vision system for detection of pedestrian on jetson nano devlopment board - Horma, Taher; Zemmit, mustapha; Kious, Mecheri (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2020)
Pedestrian detection is one of the important fields of object detection and computer vision. It is being applied in a wide range of applications such as video surveillance, automated driving, etc. In this work we show how to create a real-time multiple object detection such as pedestrians and recognition application in Python on the Jetson Nano developer kit using a camera and deep learning models and libraries that Nvidia provides.
OPTION: Embedded Systems